The Educational Technology of Monological Speaking Skills Formation of Future Lawyers - Nadezhda Almazova; Oksana Sheredekina; Maria Odinokaya; Natalia Smolskaia (MDPI AG, 2021)
In modern higher education, there was a change in the educational paradigm, when the emphasis shifted to the formation of competencies. The goal of the competence approach is to improve the quality of education, which is impossible without the use of educational technologies that guarantee a steady effective result. The priority of teaching foreign languages to future lawyers is the foreign speaking skills formation in general and the monological ones in particular. The introduction of educational technology in the process of monological speaking skills formation, including a set of methods and techniques such as peer review, discussion, working with the text, etc., took place over the course of the pedagogical experiment. Qualitative and quantitative data analysis allowed us to determine the difference in the level of the monological speaking skills formation in experimental and control groups at all stages of the experiment conducted. The effectiveness of the developed technology is determined by the significance of the adaptation stage, the use of the peer review method, which implements the potential of students' metacognitive skills, and the possibility to change the role while evaluating students' answers.